1999
DOI: 10.1359/jbmr.1999.14.4.609
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Bone Resorption During the Menstrual Cycle

Abstract: To determine if the cyclic changes of female sex hormones during the menstrual cycle are related to changes in bone formation and resorption, we measured serum bone-specific alkaline phosphatase (BAP) and osteocalcin (OC) and bone resorption markers, serum and urine deoxypyridinoline (Dpyr), three times per week during one menstrual cycle in 20 healthy premenopausal women. Serum estradiol (E 2 ) and progesterone (P) showed characteristic cyclic fluctuations. Serum Dpyr was higher during the follicular phase (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 39 publications
5
33
0
Order By: Relevance
“…As previously reported in other studies of bone formation markers including P1NP (23)(24)(25), we found that serum automated total P1NP concentrations decreased from age 30 to 35 years and then remained stable up to 50 years in healthy premenopausal women. The higher values in younger women probably reflect the fact that skeletal maturity has not yet been achieved, especially at the cortical sites, a time of increased bone turnover.…”
Section: Discussionsupporting
confidence: 89%
“…As previously reported in other studies of bone formation markers including P1NP (23)(24)(25), we found that serum automated total P1NP concentrations decreased from age 30 to 35 years and then remained stable up to 50 years in healthy premenopausal women. The higher values in younger women probably reflect the fact that skeletal maturity has not yet been achieved, especially at the cortical sites, a time of increased bone turnover.…”
Section: Discussionsupporting
confidence: 89%
“…Much of the variability is likely to be related to cyclic fluctuations of female sex hormones. Biochemical markers of bone resorption are clearly influenced by fluctuations in these hormones [10,23,48]. In one study, PYD varied as much as 50% from 3 days after ovulation to day 3 of the follicular period of the same menstrual cycle [48].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the menstrual cycle on markers of bone turnover is small [175,176]. Zitterman et al [177] have recently reported a signi®cant menstrual rhythm in deoxypyridinoline and pyridinoline excretion with an amplitude of 33% and 32% respectively and a nadir in the early luteal phase.…”
Section: Menstrualmentioning
confidence: 99%